Pension Reform in Norway. Microsimulating effects on government expenditures, labour supply incentives and benefit distribution - Kyrre Stensnes; Nils Martin Stølen (Statistics Norway, Research Department, 2007)
A much higher old-age dependency ratio, together with more generous pension benefits, will lead to a substantial increase in the future public pension expenditures burden in Norway. A pension reform implemented from 2010 will imply a shift to a quasi-actuarial system, seeking to neutralise the expenditure effect of further growth in life expectancy and strengthen ties between former earnings and pension benefits. Labour supply will be stimulated by lowering implicit tax rates and by aligning the social and private costs of early retirement. Using a large dynamic microsimulation model we find that the reform will stimulate labour supply and reduce the future tax burden, but also increase inequality in the benefits received by old age pensioners.
Keywords: H53; H55; J26; 330; Pension reform; social security; retirement; pension expenditures